PELATIHAN MELAKSANAKAN PTK UNTUK GURU MI FATHUL UMUM DI KECAMATAN MUNCAR KABUPATEN BANYUWANGI: CLASSROOM ACTION RESEARCH TRAINING FOR TEACHERS AT MI FATHUL ULUM IN MUNCAR BANYUWANGI - Rohana Sufia; Mohamad Anas; Mochamad Sulaiman (STAI Al Fithrah Press, 2022)
The community service program is one of the obligations that must be carried out by lecturers (researchers/writers). Training to carry out classroom action research with MI Fathul Ulum as a partners is one of the way for the lack of awareness of teachers regarding increasing their competence in schools. This community service program activity is divided into three phases or stages, these are planning, implementation, and final evaluation using a participatory action research (PAR) approach. PAR has advantages as a type of community service program approach or method because PAR is mutually beneficial by solving the most urgent problems in school partner, it was problems related to learning. After the community service program activity was completed, it was not only the researchers who benefited but other parties also benefited, namely; partner schools, teachers, and students. Keywords: training, classroom action research